EFFECTIVENESS OF TEACHING COPING STYLES ON MARITAL SATISFACTION, SELF-EFFICACY AND PSYCHOLOGICAL WELLBEING OF COUPLES: Life Science - Psychological - KHALEGHIAN, REZA; KHOSHNEVIS, ELAHEH; VATANKHAH, HAMIDREZA (International Journal of Life Science and Pharma Research, 2017)
Considering the increasing changes and development of social relations in contemporary era, preparing people, particularly young couples, to cope with life predicaments is a vital need. The present research seeks to determine the effectiveness of teaching coping styles on marital satisfaction, self-efficacy, and psychological wellbeing on couples.This is an interventional, quasi-experimental research using pretest – posttest with control group. The research population included all couples resorting to psychological counselling centers of Tehran from March to September 2016. The research sample consisted of 30 couples (60 participants) who took part in the research voluntarily and with due knowledge of the process. They were randomly divided into the case and control group. All participants responded to Enrich’s marital satisfaction questionnaire, Ryff’s psychological wellbeing questionnaire, Shrer’s general self-efficacy questionnaire and the questions associated with demographic specifications both before and after intervention. To analyze the resulting data, first descriptive statistics of mean, standard deviation, and then covariance analytical method in line with inferential analysis were utilized.Covariance analysis has shown that the effect of coping styles on marital satisfaction (F (1 & 58) =233.65, P<0.001, Partial η 2=0.80), couples’ communication (F (1 & 58) =62.56, P<0.0001, Partialη 2=0.51), conflict resolution (F (1&58) =4.98, P<0.0001, Partial η 2=0.22), ideal distortion (F (1 & 58) =5.19, P<0.01, Partial η 2=0.33), selfefficacy (F=58.17, P<0.01, Partial η 2=0.50), psychological well-being (F (1 & 58) =268.13, P<0.0001, Partial η 2=0.82), self-acceptance (F (1 & 58) =118.72, P<0.0001, Partial η 2=0.67), positive relations with others (F (1 & 58) =62.36, P<0.0001, Partial η 2=0.51), autonomy (F (1 & 58) =232.98, P<0.0001, Partial η 2=0.80), purposefulness in life (F (1 & 58) =208.21, P<0.0001, Partial η 2=0.78), personal growth (F (1 & 58) =163.50, P<0.0001, Partial η 2=0.73), environmental mastery (F (1 & 58) =112.29, P<0.0001, Partial η 2=0.65) is significant. As the results of the present research indicate, instructing coping styles has increased marital satisfaction, self-efficacy, and psychological wellbeing among couples. In a theoretical level, the results of the present research confirm the results of previous researches. In a practical level, the results of the present research can be used to develop educational and therapeutic programs.